2004
DOI: 10.1007/s00013-004-1040-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiplication operators on Hilbert spaces of analytic functions

Abstract: Let H be a Hilbert space of functions analytic on a plane domain such that for every λ in the functional of evaluation at λ is bounded. Assume further that H contains the constants and admits multiplication by the independent variable z, M z , as a bounded operator. We give sufficient conditions for M z to be reflexive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In the rest of the paper we assume that X is a Banach space of analytic functions on the open unit disc U satisfying the conditions that come in the introduction. For some works on these topics see [1][2][3][4][5][6][7]. Assume, further that the composition operators C aϕ are bounded and invertible on X where ϕ is a multiplier of X and 0 < |a| ≤ 1.…”
Section: Resultsmentioning
confidence: 99%
“…In the rest of the paper we assume that X is a Banach space of analytic functions on the open unit disc U satisfying the conditions that come in the introduction. For some works on these topics see [1][2][3][4][5][6][7]. Assume, further that the composition operators C aϕ are bounded and invertible on X where ϕ is a multiplier of X and 0 < |a| ≤ 1.…”
Section: Resultsmentioning
confidence: 99%
“…Let Y =  (U)  and Z =  , then Y and Z are quasi-affinities intertwining T and M  U  T 1  T 2 and satisfying ZY = (M) and ZY = (T) c.f. [16] theorem 2.1) [17]. For K  Lat T. The mappings K  and L  L preserve the lattice operations in Lat T and Lat M and are inverse to each other.…”
Section: Theoremmentioning
confidence: 99%
“…In [26] it is shown that any powers of the operator M z is reflexive on Banach spaces of formal Laurent series. Also, reflexivity of the multiplication operators on some function spaces has been investigated in [6,10,11,20,24,27]. In this article we would like to give some sufficient conditions so that the powers of the operator M z , acting on Banach function spaces becomes reflexive.…”
Section: Introductionmentioning
confidence: 99%